Melatonin, Autophagy and Intestinal Bowel Disease - Talero, Elena; Garcia-Maurino, Sofia; Motilva, Virginia (Current Pharmaceutical Design, 2014)
The intestinal epithelium forms a barrier against the intestinal contents and the wider environment, allowing entry of selected molecules for nutrition and programming of the mucosal immune system, but excluding toxins and most microorganisms. Many receptors and signalling pathways are coupled and implicated in the epithelial control and significant advances have been achieved in the understanding of the pathogenesis of inflammatory bowel disease (IBD) and in the introduction of biologics. However, not all of the patients respond and many lose their response. Data from experimental studies have documented that the pineal secretory product melatonin exerts important inmunoregulatory and antiinflammatory effects in different models of colitis. These actions have been associated to a variety of mechanisms, such as reduction of T cells number, modulation of macrophage activity, suppression of NFκB activity, inhibition of cell adhesion molecules and proinflammatory cytokines , suppression of COX-2 and iNOS levels and the consequent synthesis of PGE2 and NO, reduction of matrix metalloproteinase (MMP) -2 and -9 activity, and modulation of apoptosis. In addition, the beneficial effects of melatonin in IBD are related to its scavenger effect on free radicals and the activation of several antioxidant enzymes. However, only a small number of human studies report possible beneficial and also possible harmful effects of melatonin in case reports and clinical trials. There is a considerable bulk of information supporting the connection between autophagy and human diseases, including IBD, and although autophagy is actually considered more a pro-survival than a pro-death pathway, these two features of its action are relevant in human diseases, having therapeutic potential for both activators and inhibitors of autophagy. Some of the opposite effects than have been reported for melatonin in IBD could be related to the duality of its effects on autophagy, which itself can be beneficial or detrimental. In this review, new data for melatonin in IBD are discussed, trying to provide recent information of different molecular mechanism including the role of the autophagy regulation.
Keywords: chronic inflammation